vector competence of Australian Culex annulirostris with Murray Valley encephalitis and Kunjin viruses - Kay, B.H; Fanning, I.D; Carley, J.G (Australian journal of experimental biology and medical science, 1984)
Australian populations of Culex annulirostris Skuse from 10 localities, Brisbane, Townsville, Cairns, Charleville, Kowanyama (Queensland), Darwin (Northern Territory), Mildura (Victoria) and Port Hedland, Karratha and Mt. Tom Price (Western Australia) showed considerable heterogeneity in response to oral infection with low passage level Murray Valley encephalitis (MVE) and Kunjin (KUN) viruses. However, there was no consistent pattern of either high or low vector efficiency for populations collected from different regions. Overall, Cx annulirostris was a more competent vector of MVE virus than KUN virus, both in oral susceptibility (suckling mouse intracerebral ID50 of 10(1.7)-10(3.9) compared to 10(2.7)-10(4.8)/mosquito, respectively) and in ability to transmit virus to chicks after 10 d extrinsic incubation (50-89% compared to 0-55%). High or low susceptibility with one virus did not correlate with susceptibility for the other. Although these date were probably subject to some seasonal variation, they generally support the view that Cx annulirostris is the principal vector of MVE in Australia. Poor to moderate susceptibility with KUN suggests that (1) it is only a minor vector in some localities, (2) vertebrate hosts have high viraemias or (3) the strain used may have been atypical.